2004
DOI: 10.1038/nsmb841
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-assisted catalysis of peptide bond formation by the ribosome

Abstract: The ribosome accelerates the rate of peptide bond formation by at least 10(7)-fold, but the catalytic mechanism remains controversial. Here we report evidence that a functional group on one of the tRNA substrates plays an essential catalytic role in the reaction. Substitution of the P-site tRNA A76 2' OH with 2' H or 2' F results in at least a 10(6)-fold reduction in the rate of peptide bond formation, but does not affect binding of the modified substrates. Such substrate-assisted catalysis is relatively uncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
298
2
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(346 citation statements)
references
References 39 publications
29
298
2
15
Order By: Relevance
“…Guided by PTC components, the rotatory motion facilitates peptide-bond formation and nascent-chain elongation. Furthermore, this motion places the A-site nucleophilic amine and the P-site carbonyl carbon at a distance allowing for interactions with the P-site tRNA A76 O2Ј throughout a significant part of the rotatory motion (3), consistent with its suggested participation in peptide-bond formation catalysis (8). The nascent proteins are directed by the rotatory motion into the exit tunnel at extended conformation, fitting the tunnel's narrow opening.…”
mentioning
confidence: 66%
“…Guided by PTC components, the rotatory motion facilitates peptide-bond formation and nascent-chain elongation. Furthermore, this motion places the A-site nucleophilic amine and the P-site carbonyl carbon at a distance allowing for interactions with the P-site tRNA A76 O2Ј throughout a significant part of the rotatory motion (3), consistent with its suggested participation in peptide-bond formation catalysis (8). The nascent proteins are directed by the rotatory motion into the exit tunnel at extended conformation, fitting the tunnel's narrow opening.…”
mentioning
confidence: 66%
“…It seems beyond doubt that the proton transfer in this reaction has to occur via the O2′ of the P-site substrate A76 ribose (22). The easiest way in which this could happen is through a six-membered transition state where the O2′ acts as a proton shuttle (15,16,20,28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed considerable progress in our understanding of the peptidyl transfer process due to high-resolution crystallographic structures of the large ribosomal subunit with transition state (TS) analogs (1), as well as kinetic measurements (2)(3)(4)(5)(6)(7)(8)(9), mutagenesis data (4,(10)(11)(12)(13)(14), and computational studies (15)(16)(17). Hence, the current model of the peptidyl transfer reaction is that ribosomal nucleobases are not directly involved in bond making or breaking through acid-base catalysis (4,10,11,13,18,19), but that the A76 2′-OH group of the P-site substrate plays a key role in mediating proton transfer from the attacking nucleophile to the leaving 3′ ester oxygen (1,15,(20)(21)(22). Furthermore, it was shown that the lower free energy barrier for the ribosome reaction, compared to an uncatalyzed reference reaction in water, is entirely due to a less negative activation entropy (3,6,7).…”
mentioning
confidence: 99%
“…Ribozymes are catalytic RNA molecules, some of which catalyse extremely important cellular reactions, notably processing tRNA and mRNA (1) and condense amino acids to form polypeptides (2)(3)(4)(5). Ribozymes are very widespread; for example ribonuclease P (6, 7) processes precursor tRNA in all domains of life.…”
mentioning
confidence: 99%